A study on the effectiveness of Global Zakat Game (GZG) as a zakat teaching and learning tool - Zainuddin, Nurkhamimi; Ab Rahman, Azman; Sahrir, Muhammad Sabri; Abd Khafiz, Hasanah (Human Resource Management Academic Research Society (www.hrmars.com), 2019)
Board games have become one of the useful tools in teaching and learning. Many instructors and educators have chosen to use board games to enhance the way of delivering course contents. An effective board game will help students understand the concept quickly and get involved in experiential learning, where students can manage and solve problems in an actual situation. This study will focus on the effectiveness of board games, namely Global Zakat Game (GZG) as a Zakat teaching and learning tool. A questionnaire has been used to analyze the effectiveness of using GZG as a Zakat teaching and learning tool in increasing students’ comprehension and understanding on Zakat concepts. The respondents gave a few suggestions and comments on how to improve the GZG for the betterment of the Zakat teaching and learning. The result obtained indicated that the use of GZG as a Zakat teaching and learning tool has a positive impact on students’ learning as it helps students learn about Zakat concepts. A majority of the respondents mentioned that they enjoyed playing GZG as it utilizes experiential learning and can be used as an edutainment tool for students and society that is suitable for all ages.